Effect of medical and surgical management and dry eyes in Eastern Odisha - Panda, Tarun Kumar; Kumari, Suchitra (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Dry eye condition has multi-factorial origin and most of the times missed or left untreated leading to resistance in its treatment modalities. Various studies had been conducted with conflicting outcomes. Dry eyes condition being more prevalent in Odisha, there is very limited published data on its management. Hence this study was conducted to evaluate the efficacy and outcome of medical and surgical management of dry eye cases due to different aetiologies. Methods: Patients were selected from those who attended ophthalmology, Skinand VD, O and G and Paediatrics OPD. Their tear film parameters like Tear film breakup time, tear meniscus height, Schirmer test, Rose Bengal stain were assessed at baseline level. Thereafter they were put on medical therapy for 6 weeks followed by appropriate surgical intervention like amniotic membrane graft, punctual occlusion, use of Symblepharon shell in resistant cases -which again was reviewed by analysis of tear film parameters. Results: Majority of patients (75% approx.) responded well to medical therapy. non responders were due to Steven Johnson syndrome, Vitamin A deficiency, KCS and systemic association. These patients underwent surgical management with follow up after 6 weeks. After 6 weeks of surgical therapy 80% cases showed improvement, while few cases due to SJS showed poor response. Conclusions: The medical modality of treatment was found to be the primary approach with better efficacy in majority of dry eye cases predominantly in mild to moderate severity. Surgical interventions proved more efficacious in severe degree of presentation.